2011
DOI: 10.1007/s10803-011-1180-6
|View full text |Cite
|
Sign up to set email alerts
|

Judgments of Cause and Blame: Sensitivity to Intentionality in Asperger’s Syndrome

Abstract: Sensitivity to intentionality in people with Asperger's syndrome (AS) and matched controls was investigated using two scenario-based tasks. The first compared intentional and unintentional human actions and physical events leading to the same negative outcomes. The second compared intentional actions that varied in their subjective and objective likelihood of bringing about a negative outcome. Whilst adults with AS did not differ from controls in their judgments of causality, or in their blame judgments in rel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
17
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 35 publications
1
17
0
Order By: Relevance
“…However, it was also considered possible that the high AQ group might differentiate more than the low AQ group between the clear-cut and ambiguous conditions in their sympathy ratings and likelihood of helping, showing more ‘black and white’ thinking consistent with a rigid reliance on social rules. In support of this prediction, some previous work with individuals with ASD reported that they showed heightened sensitivity to ‘good’ versus ‘poor’ justifications for wrongdoing (Channon et al 2010 ), and greater differentiation between intentional and unintentional actions when assigning blame (Channon et al 2011 ).…”
Section: Introductionmentioning
confidence: 77%
See 1 more Smart Citation
“…However, it was also considered possible that the high AQ group might differentiate more than the low AQ group between the clear-cut and ambiguous conditions in their sympathy ratings and likelihood of helping, showing more ‘black and white’ thinking consistent with a rigid reliance on social rules. In support of this prediction, some previous work with individuals with ASD reported that they showed heightened sensitivity to ‘good’ versus ‘poor’ justifications for wrongdoing (Channon et al 2010 ), and greater differentiation between intentional and unintentional actions when assigning blame (Channon et al 2011 ).…”
Section: Introductionmentioning
confidence: 77%
“…Some previous work has reported ‘black and white’ sympathy ratings in those with ASD, with heightened sensitivity to ‘good’ versus ‘poor’ justifications for wrongdoing (Channon et al 2010 ), and greater differentiation between intentional and unintentional actions when assigning blame (Channon et al 2011 ). No evidence of such ‘black and white’ thinking was found in the present AQ study, since sympathy ratings were lower overall in the high versus low AQ group, and the groups were not differentially affected by the strength of the social rule.…”
Section: Discussionmentioning
confidence: 99%
“…This explanation could also account for the absence of differences in awkwardness ratings between groups in the present study; individuals with AS may have made simple judgements of this nature on the social knowledge and social conventions they had explicitly learnt through experience. Studies examining social reasoning in individuals with AS has shown that their thinking can in fact often appear more rule based and “black and white” compared to healthy individuals, especially when they are asked to reason about more complex social situations requiring the appreciation of multiple social and emotional factors (Channon et al, 2010, 2011; Grant et al, 2005; Moran et al, 2011; Shulman et al, 2012). Thus, reliance on social expectations and conventions when evaluating or responding to awkward situations such as in the present study could lead to a discrepancy between knowledge that a situation is conventionally seen as appropriate versus inappropriate, and comprehension of the reasons behind this.…”
Section: Discussionmentioning
confidence: 99%
“…Channon, Fitzpatrick, Drury, Taylor, and Lagnado (2010) found that individuals with AS tended to make more marked distinctions than controls between more valid and poorer justifications in their sympathy judgements for drivers causing car accidents. Similarly, those with AS were found to differentiated more markedly between intentional and unintentional human actions than controls in assigning blame for negative outcomes (Channon, Lagnado, Fitzpatrick, Drury, & Taylor, 2011). Moran et al (2011) also examined intentionality, and concluded that individuals with HFA relied more on outcome information than on characters’ intentions when judging the moral permissibility of actions described in a series of vignettes.…”
Section: Introductionmentioning
confidence: 99%
“…They make greater differentiation between intentional and unintentional actions as compare to controls. They also better differentiate between actions with likely protagonists believed versus unlikely ones that lead to negative consequences ( Channon, Lagnado Fitzpatrick, Drury, & Taylor, 2011 ).…”
Section: Cognitive Markers Of Asperger Syndromementioning
confidence: 99%